USE INFORMATION TECHNOLOGY IN THE PROCESS OF PERFORMING PHYSICAL ACTIVITY IN PRESCHOOLERS (American Journal of Technology and Applied Sciences, 2024)
This article will consider examples of the use of information and communication technologies in the field of physical development in a preschool organization.